Are Teachers Paying Enough Attention to Low-achieving Students While Teaching Reading Strategies? - Sičiūnienė, Viktorija; Toleikytė, Nijolė (Pedagogika, 2017)
The article presents the results of the qualitative research on the attitude of teachers towards low-achieving students while teaching reading strategies. Such scientific studies have not been conducted in Lithuania before. This was the first research, which aimed to identify if the teachers allocated attention to low-achieving school learners while reflecting on the process of teaching/ learning reading strategies and the achieved results. The sample of the research included 33 teachers from Lithuanian schools. They were participants in the national project “Learning Teachers – Learning Students” in 2015–2016. For two years it was observed how teachers in cooperating teams learned to apply reading strategies and provided collegial feedback to each other. The authors of the article were experts, who prepared diagnostic tests measuring reading skills, provided recommendations to the teachers how to apply methodology for teaching reading strategies, to measure and analyse reading achievements. The research results revealed that not all the teachers of the Lithuanian language and mathematics repeatedly measured reading skills of their learners. The teachers’ responses show that the total dynamics of results of project schools is evaluated positively but in separate cases it is quite ambiguous. It was noticed that evaluating the dynamics of reading results, the focus is laid more on the average indicator in the class and too little attention is paid to monitoring and analysis of the results of separate learner groups, and on those of low-achieving students in particular, as well as to individual progress of learners. Analysing the teachers’ reflections on how decisions/agreements about application of specific reading strategies are made, it can be stated that collegial feedback, agreements at school level and colleagues support was particularly important to teachers but it lacked a focused orientation, too little attention was dedicated to observation and discussion of practice of reading strategy application.